Does investment in human capital via the completion of a certificate-level post-school qualification pay off for early school leavers’ - Chesters, Jenny (My University, 2013)
Employment options for young school leavers have diminished as service sector jobs replaced manufacturing sector jobs and opportunities for low-skilled employment became concentrated in the retail and hospitality sectors. Young people with low levels of education are less likely to be employed and if employed, are less likely to be working full-time. Currently, the unemployment rate of those aged between 15 and 19 years is around 17% and of those who are employed, just 29% are employed on a full-time basis. Drawing on Human Capital Theory, this paper examines the association between educational qualifications and employment status, occupational prestige and earnings for young people using the first 10 waves of the Household Income and Labour Dynamics in Australia (HILDA) data. The results show that payoffs to investment in human capital differ according to gender with completing Year 12 providing the best returns, in terms of full-time employment, for females and completing certificate level qualifications providing the best returns, in terms of full-time employment, for males.
Keywords: Human Capital -- Education; Education and Training -- Educational level; Human Capital; Human Capital -- Labour; Learning, education and training; Education and Training; Human Capital; Education; Labour; Educational level; Learning, education and training